In defence of open-mindedness - Hare, William (McGill-Queen's University Press, 1985)
William Hare believes that open-mindedness - the disposition to form a belief, and if necessary to revise or reject it, in the light of available evidence and arguement - stands in need of a defence because it is under widespread attack. In this sequel to his highly regarded Open-mindedness and Education [1979], he examines the numerous ways in which opposition to open-mindedness is expressed, and shows how these criticisms can be countered. He argues that the general indictment of open-mindedness as a habit of mind leading to nihilism and scepticism, as well as to neglect of the emotions, is based upon a misunderstanding of the nature of the concept, which in his opinion is by no means incompatible with personal commitment and confidence. Similar confusions are exposed in such areas as elementary schooling, moral education, educational standards, methods of teaching, the administration of schools, and the teaching of science. In each of these areas, examples are taken from the writings of influential critics to illustrate the nature of the doubts concerning open-mindedness - doubts that are carefully analysed and show to rest ultimately upon erroneous assumptions. And since he believes that many who set out to champion open-mindedness manage to confuse this ideal with other notions, Hare undertakes in a concluding chapter to protect the ideal from its would-be friends and supporters.